FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMSI PRODUK HALAL PADA KALANGAN MAHASISWA MUSLIM - Nurul Huda; Hulmansyah Hulmansyah; Nova Rini (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2018)
The purpose of this study is to examine the factors of knowledge, attitude, subjective norms, behavioral control, and religious commitment to influence behavior through intentions for consumption of halal products. Based on the literature review, this research hypothesis states that knowledge, attitudes, subjective norms, behavioral control, and religious commitment affect the behavior through intention. This study uses survey data from questionnaires to 150 respondents. Hypothesis testing technique is done by using SEM analysis with Lisrel software. The results of data processing indicate that Knowledge, Attitudes, Subjective Norms, Behavior Control, and Religious Commitment have a significant influence on behavior through intention to consume halal products. Intensi variables have a significant influence on the consumption behavior of halal products with t value of 7.14. Behavior Control and Religious Commitment have a greater influence on behavior through intention to consume halal products than other variables. Suggestions based on the results of research: first, need to consciously consume halal products by increasing one's religious commitment. Second, it needs to be enhanced the role of society both from internal and external in controlling one's behavior to consume halal product.